Risk of acute pericarditis after pulsed-field ablation pulmonary vein isolation - Juliana Pérez-Pinzón, MD; Shu Yang, MD; Timothy Maher, MD; Andrew H. Locke, MD; Peter Zimetbaum, MD; Kapil Kumar, MD; Alexei Shvilkin, MD; Charles I. Haffajee, MD; Alfred E. Buxton, MD; Andre d’Avila, MD; Gregory F. Michaud, MD, FHRS; Jonathan W. Waks, MD; et al. (Heart Rhythm O2)
Background: Postablation pericarditis (PAP) can occur after pulmonary vein isolation (PVI) using radiofrequency ablation (RFA). Pulsed-field ablation (PFA) PAP is anticipated to be lower based on its nonthermal nature and initial studies. Objective: We aimed to evaluate the incidence of PAP after PFA and compare this with rates of RFA PAP. Methods: We prospectively identified cases of PAP in 322 patients who underwent PFA PVI ablation between April 2024 and December 2024 and 1750 patients who underwent RFA PVI between January 2022 and December 2024. Logistic regression was used to assess factors associated with PAP. Results: Acute pericarditis occurred in 14 PFA patients and 60 RFA patients (4.3% vs 3.4%, P = .41). Median time to PAP presentation was 4 days for PFA and 1 day for RFA (P = .12). For PFA, symptoms were remotely managed in 50% of cases and via unplanned outpatient evaluation in 36% of cases. There was no significant difference in triage strategies or the need for a revisit owing to persistent symptoms between energy types. For treatment of PAP, colchicine alone was used more frequently, and both steroids and acetaminophen alone were used less frequently after RFA compared with PFA, although these differences were not statistically significant. After adjustment, female sex and obstructive sleep apnea were associated with an increased risk of PAP, whereas having a previous ablation and older age decreased this risk. Conclusion: Rates of PFA PAP are higher than initially estimated and similar to RFA PAP, with similar risk factors.